A study of the weathering of the Seremban granite - Ghiasi, Vahed; Omar, Husaini; Kim Huat, Bujang (Electronic Journal of Geotechnical Engineering, 2009)
This paper presented the weathering profile, modulus of elasticity and compressive strength of weathered granite in Seremban, Malaysia. The granite of Seremban is found to exhibit a full range of weathering grades. With increased weathering, the modulus of elasticity and uniaxial compressive strength of the granite is found to decrease.